Snail-1 Silencing by siRNA Inhibits Migration of TE-8 Esophageal Cancer Cells Through Downregulation of Metastasis-Related Genes - Maryam Hemmatzadeh; Hamed Mohammadi; Farhad Babaie; Mehdi Yousefi; Mehrdad Ebrazeh; Behzad Mansoori; Dariush Shanehbandi; Behzad Baradaran (Tabriz University of Medical Sciences, 2018)
Purpose: Snail-1 is a transcription factor, which takes part in EMT, a process related to the emergence of invasion and cancer progression. The purpose of this study was to evaluate the effect of Snail-1 silencing on the human esophageal squamous cell carcinoma cell line, namely TE-8, in vitro. Methods: In this study, transfection of Snail-1 specific siRNA was conducted into TE-8 cells. The relative mRNA expression levels of Snail-1, Vimentin, CXCR4 and MMP-9 and transcription levels of miR-34a and let-7a were investigated by quantitative Real-time PCR. Western blotting was carried out to evaluate the Snail-1 protein level. Migration assay of TE-8 cells was also performed following the presence or absence of Snail-1 specific siRNA. MTT and TUNEL assays were performed to evaluate cell viability after Snail-1 silencing. Results: It was found that treatment of cancer cells with the Snail-specific siRNA effectively downregulated the expression of Snail-1 in both mRNA and protein levels, and vimentin, CXCR4, and MMP-9 in mRNA level. However, it elevated the transcript levels of miR-34a and let-7a expressions. Furthermore, transfection of cancer cells with the Snail-specific siRNA significantly induced apoptosis in TE8 cells. Moreover, suppression of Snail-1 led to diminished cell migration. Conclusion: It seems that Snail-specific siRNA can significantly interrupt esophageal cancer cell migration and reduce metastatic-related factors and induce miR-34a and let-7a in vitro. The bottom line is that therapeutic approaches via targeting Snail-1 can be used for ESCC treatment, suggesting that other possible target molecules for ESCC therapy require to be explored.